Strengthening of pipe tools for cold roller rolling of corrosion-resistant pipes by application of amorphous alloys - Krivchik, L.; Khokhlova, T.; Pinchuk, V.; Holovachov, А.; Srebryansky, G.; Nosenko, V.; Zagorodniy, O. (Вопросы атомной науки и техники, 2021)
In the production of pipes from corrosion-resistant steels on pipe rolling plants, the current problem is the low stability of the pipe tool. Therefore, the creation of high-performance and durable tools is associated primarily with the production and processing of materials that could withstand harsh working conditions. The technology of heat hardening of the pipe tool for cold roller rolling of corrosion-resistant pipes (rollers and support laths of HPTR mills) from 4Х5МФ1С steel which excludes the third holiday and uses drawing of a covering from powders of amorphous alloys 100…150 µm thick is offered in the work. As a result of the offered technology durability, wear resistance, and also hardness to HV0.1 950–1050 (in comparison with HV 587–690 on existing technology of heat treatment in factory conditions) increases. A wide range of studies of the structure of the coating and industrial tests of rollers and support bars. It is shown that gas-plasma coating of amorphous alloy based on Fe–Si–B system increases the hardness of the tool surface by 1.3–1.6 times and their stability by ~ 30…50%. При виробництві труб із корозійно-стійких сталей на трубопрокатних установках актуальною проблемою є низька стійкість трубного інструменту. Тому, створення високопродуктивних і стійких в експлуатації інструментів зв'язане у першу чергу з одержанням й обробкою таких матеріалів, які могли б протистояти жорстким умовам роботи. В роботі запропонована технологія термозміцнення трубного інструмента для холодної роликової прокатки корозійно-стійких труб (роликів і опорних планок станів ХПТР) зі сталі 4Х5МФ1С, яка виключає третій відпуск і використовує нанесення покриття із порошків аморфних сплавів товщиною 100…150 мкм. Внаслідок запропонованої технології підвищуються міцність, зносостійкість, а також твердість до HV0,1 950–1050 (в порівнянні із HV 587–690 за існуючою технологією термічної обробки в заводських умовах). Проведено широкий комплекс досліджень структури покриття і промислових випробувань роликів і опорних планок. Показано, що газоплазмове нанесення покрить з аморфного сплаву на основі системи Fe–Si–B збільшує твердість поверхні інструменту в 1,3–1,6 рази і їх стійкість на ~ 30…50%. При производстве труб из коррозионно-стойких сталей на трубопрокатных установках актуальной проблемой является низкая устойчивость трубного инструмента. Поэтому создание высокопроизводительных и устойчивых в эксплуатации инструментов связано в первую очередь с получением и обработкой таких материалов, которые могли бы противостоять жестким условиям работы. В работе предложена технология термоупрочнения трубного инструмента для холодной роликовой прокатки коррозионно-стойких труб (роликов и опорных планок станов ХПТР) из стали 4Х5МФ1С, которая исключает третий отпуск и использует нанесения покрытия из порошков аморфных сплавов толщиной 100…150 мкм. Вследствие предложенной технологии повышаются прочность, износостойкость, а также твердость до HV0,1 950–1050 (по сравнению с HV 587-690 по существующей технологии термической обработки в заводских условиях). Проведен широкий комплекс исследований структуры покрытия и промышленных испытаний роликов и опорных планок. Показано, что газоплазменное нанесениe покрытий из аморфного сплава на основе системы Fe–Si–B увеличивает твердость поверхности инструмента в 1,3– 1,6 раза и их устойчивость на ~ 30…50%.